The mediating effect of power and trust in the relationship between procedural justice and tax compliance - Sellywati Mohd Faizal,; Mohd Rizal Palil,; Ruhanita Maelah,; Rosiati Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Various factors have been identified by researchers in Malaysia which may influence tax compliance behavior for example tax complexity; compliance costs; penalties; and tax knowledge. Yet, it is still unable to minimize tax non-compliance. Thus, this research identifies other factors, if any and their effect on Malaysian tax compliance behavior. The factors are procedural justice, trust and power. As far as known, no study in Malaysia examines the effect of these factors on tax compliance in a single study. Studies conducted outside Malaysia have found that procedural justice has a significant and positive relationship with tax compliance. In addition, there are also studies which described that procedural justice has the relationship with trust and legitimate power. Therefore, the objective of this study is to examine the relationship between procedural justice and compliance with the existing of trust and power as mediator. Structural Equation Model (SEM) is used to analyze the data that has been collected from 241 respondents. The findings suggest that procedural justice and trust have a positive relationship with tax compliance. Moreover, the bootstrapping approach found that trust could be a mediator in the relationship between procedural justice and tax compliance. In contrast, neither legitimate power nor coercive power influence tax compliance and mediate the relationship between procedural justice and tax compliance.